Development of Sustainable Logistics for Indonesian Remote and Rural Islands Connectivity: A Case Study of the Anambas Islands Regency - Kuncoro Harto Widodo; Anjar Kistia Purwaditya; Joewono Soemardjito (Faculty of Geography, Universitas Gadjah Mada, 2021)
Usually, countries have a fundamental problem in fulfilling remote and rural island inhabitants’ logistical needs. This study was aimed to analyze the performance of logistics systems in Indonesian remote and rural islands by focusing on the Anambas Islands Regency case. We proposed a House of Sustainable Logistics method by considering and combining the framework used in the House of Quality based on the variable of sustainable logistics systems (profit, people, and the planet) with the variables of seven key general logistical drivers (infrastructure, information and communication technology, human resources, logistics service providers, regional laws and regulations, regional institutions, and key commodities.). The study results indicated five key aspects of potential prime movers to be developed (ASLDPj value = 54); they are infrastructure, human resources, logistics service providers, local laws and regulations, and key commodities.